Prevalence, Serotypes And Pathogenicity Of Escherichia Coli Associated With Diarrhoea In Dairy Calves - Udaykar, Aniruddh; Sharda, Rakesh (Indian Journal of Veterinary Sciences and Biotechnology, 2014)
Sixty two (53.44%) strains of E. coli were isolated from 116 fecal samples collected from cow and buffalo calves suffering with diarrhoea. Biochemical characterization revealed 9.6% atypical strains, which were weakly urease positive. The isolates of E. coli were typed into 27 different ‘O’ serotypes. 4 strains were untypable, while 2 were rough. Whole bacterial cultures as well as cell free filtrate of randomly selected E. coli strains of O2, O14, O15, O28, O60, O69, O138, and 0171 serotypes and one untypable strain caused mortality in mice on intraperitoneal inoculation.